Effect of Locally available Organic Manures on the Growth and Yield of Potato in Bajhang District - Rai, Sapana; Bohora, Anisha; Sharma, Raksha; Tamang, Tirsana (Journal of Agriculture and Resource Management, 2024)
Potato (Solanum tuberosum L.) is one of the significant food crops of the high hill and mountain region of Nepal. The field experiment was conducted during the month of Feb-June, 2023 at Talkot Rural Municipality-1, Bajhang district of Nepal. In the hilly region, farmers commonly use farmyard manure (FYM) in their potato crop as compared to other organic manures like goat manure, poultry manure, compost, etc. Thus, this study was carried out to investigate the effect of locally available organic fertilizers on the growth and yield of potato var. Desiree. The experiment was laid out in randomized complete block design with five treatments viz. T1: control (without organic manure), T2: poultry manure, T3: farmyard manure, T4: goat manure, and T5: compost, and each treatment was replicated four times. The recommended dose of chemical fertilizers as recommended by government of Nepal was applied in all the treatments. There were no significant differences among the treatments on plant height and leaf number in potatoes except for the plant height at 60 days of planting. Plant height was found to be the highest in the plots treated with poultry manure followed by compost manure & goat manure. Statistically, the different treatments did not show significant variation in yield. However, the highest tuber yield was obtained from compost manure followed by poultry manure, goat manure, farmyard manure, and control. Application of compost manure yielded 37.6 t/ha potato tuber which is 19.69% greater than the control which yielded 30 t/ha only. Similarly, the result concluded that the application of goat manure obtained the highest net benefit among all other organic manures in the study area.